Program for the training of cognitive activity in the elderly (Impetus, 2021)
According to demographic studies it is estimated that in 2020 the proportion of the number of elderly will be 20-25%. This aging of the population causes a notable increase in the diseases linked to aging. It has been suggested that the Cognitive Reserve is a mechanism that links high levels of learning, physical exercise and cognitive activity with a lower risk of suffering from a neurodegenerative process. The research aims to implement a program of study and training of cognitive activity in the elderly. It shows as a result the application of the program for the study and training of cognitive activity in the elderly, causing changes in aspects such as operating memory, attention, and speed of processing and executive function of the participants in the program.